Determinants of firm profitability: empirical evidence from Jordan’s service sector - Hassan Hamad Aldboush; Nashat Ali Almasria; Marah Ferdous (Business: Theory and Practice, 2023)
This paper examines the financial factors affecting profitability across the listed Jordanian service companies. Insufficient attention has been paid to the influence of profitability specifically revealed by financial indicators. This study adopts the firm effect model. The investigation is established on panel data from 2015 to 2020, based on annual company reports. Regression was used to test the study hypotheses. The research sample is collected from the 46 public service firms listed. The profitability of Jordan’s service firms is measured by three proxies, including, Return on Equity (ROE), Earnings Per Share (EPS) and Return on Assets (ROA). The results reveal that firm size and liquidity positively and significantly impact profitability. Conversely, the findings verify that company efficiency and market power have no significant impact on profitability. Moreover, among Jordan’s service firms’ financial indicators, the findings confirm that neither firm nor sales growth have a significant influence on profitability, while sustainable growth rate has a positive, significant effect on profitability. The firm effects are higher for ROE than ROA and EPS. The study provides beneficial insights for managers and investors by providing effective policies designed to improve profitability. The results also provide shareholders with statistics that will ensure the profitability of companies operating in developing countries, such as Jordan.